Price volatility, speculation and excessive speculation in commodity markets: Sheep or shepherd behaviour? - Bernardina Algieri (University of Bonn, Center for Development Research (ZEF), 2012)
The present study aims to investigate the dynamics of primary commodity prices and the role of speculation over time. In particular the relationship between speculation and price volatility on the one side, and the linkage between excessive speculation and price volatility on the other side, is carefully examined with the scope to establish whether volatility drives speculation or speculation drives price volatility, or whether there are no linkages between the two variables. In order to identify the presence of any lead-lag relationships, two batteries of Granger causality tests are carried out for the period 1995-2012. The investigation complements a preliminary index analysis on speculation and excessive speculation in the commodity market. Unlike several academic researches that reject any causal relationship between the two variables, this study shows that excessive speculation drives price volatility, and that often bilateral relationships exist between price volatility and speculation. In addition, the lead-lag relationships are found not for the entire sample period 1995-2012, but when small sub-periods are taken into account. It turns out, in fact, that excessive speculation has driven price volatility for maize, rice, soybeans, and wheat in particular time frames, but the relationships are not always overlapping for all the considered commodities.
Keywords: L9; L16; O16; O2; 330; Price volatility; excessive speculation; Granger analysis; Rohstoffpreis; Volatilität; Spekulation; Herdenverhalten; Schätzung; Welt